Patient Satisfaction with Pain and Palliative Care Services in Kerala - Santha S (International Journal of Research in Social Sciences, 2014)
The main objective of the study is to analyze the patient satisfaction with Pain and Palliative Care services in Kerala. Materials and Methods The respondents of the study include Pain and Palliative care patients in the State of Kerala. The sample consisted of 871 patients comprising of 471 males and 400 females. The data collected were suitably classified and analyzed keeping in view the objectives of the study. For the purpose of analysis, statistical tools like averages, percentages, rank test and Pearson‟s Chi Square test were applied. Results Most of the male and female patients got the services of doctors, nurses and volunteers and were either highly satisfied or satisfied with the services of the doctors, nurses, volunteers and in the present medical treatment. The hope of male patients could be maintained/ strengthened through palliative care treatment and female patients experience a „Feeling of independence‟ after undergoing palliative care treatment. All the patients needed improvement in the services of the doctors and male patients needed an increase in the frequency of volunteer‟s visit whereas the female patients required an increase in the frequency nurse‟s visit.